Are financial market states recurrent and persistent? - Matthew W. Burkett; William T. Scherer; Andrew Todd (Cogent Economics & Finance, 2019)
Market participants often invoke the concept of discrete state when discussing financial markets. Bull market, bear market, depression, and recession are all terms that map to discrete market states. Mental models of how markets behave in each state and transition between states are then applied to decision-making. Implicit to that approach is the assumption that states are persistent and recurrent over time. This article seeks to formalize notions of discrete market states by proposing a parsimonious and innovative approach to segmenting periods of time into discrete states. The technique is demonstrated and evaluated in a series of case studies.
Keywords: 330; portfolio design; regimes; discrete states; clusters; modern portfolio theory; Markov; states